Perspectives on bank competition and the real economy - Ryan, Robert M. (Trinity College (Dublin, Ireland). Department of Economics, 2014)
The subject of this thesis is the empirical analysis of bank competition. An expanding collection of theoretical arguments suggests that the intensity at which banks compete with each other can influence their behaviour—and the behaviour of the economic agents with which they interact— in profound and complex ways. The implications of this evolving theory reach far beyond the traditional predictions of the industrial organisation literature as they relate to prices, quantities and economic rents. Indeed, many of these predictions have highhghted a number of previously unconsidered negative effects of increased bank competition and. as a result, the academic and public policy debate has evolved beyond the once well-established prior that competition in banking markets produces unambiguous welfare gains.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin